THE STRATEGY OF THE BANDUNG CITY’S NATIONAL UNITY AND POLITICS AGENCY IN REALIZING EXCELLENT HUMAN RESOURCES - Mursyid Setiawan; Hilal Ramdhani; Cecep Darmawan (Indonesia Defense University, 2020)
The strategy of the Bandung National Unity and Political Agency (Bakesbangpol) in realizing excellent human resources is still conventional. This can be seen in the form of education and training for the community without using technological advances to develop community digital literacy as an effort to create excellent society and protect from internal threats in the form of radicalism, terrorism, and intolerance; and externally, in the form of territorial security and digital security. The purpose of this study is to analyze the strategy of the Bandung City Political and National Unity Agency in realizing excellent human resources to face the various threats facing Indonesia. This research uses a qualitative approach with case study methods, data collection techniques using interviews, observation and documentation, then analyzed using reduction, data presentation and drawing conclusions. The results showed that the strategic concept carried out by the Bandung City Political and National Unity Agency in the form of education and training to defend the state for the community. The implementation carried out was still conventional, an alternative to realizing excellent human resources carried out by the National Unity and Political Agency, namely by optimizing the use of technology, create a sustainable curriculum and focus on developing digital literacy in society to prevent various external and internal threats.Keywords: The National Unity and Political Agency, defend the state indonesia, society, human resources